Synthesis and Structural Studies of Cr(III), Mn(II) and Fe(III) Complexes of N(2-Benzimidazolyl)acetylacetohydrazone - G. H. Anuradha; A. V. Chandra Pal (E-Journal of Chemistry)
The ligand N(2-benzimidazolyl)acetylacetohydrazone (BAAH) have been synthesized and characterized. Coordination complexes of Cr(III), Mn(II) and Fe(III) have been synthesized with the ligand BAAH. These complexes were characterized on the basis of analytical, conductance, thermal, magnetic data and infrared and electronic spectral data. The ligand BAAH is behaving as a neutral tridentate NNO donar employing two azomethine nitrogens (ring and side chain) and carbonyl oxygen. The ligand and it's metal complexes were tested for anti microbial activity on the gram positive S. Aureus, E. coli and Proteus.